2017
DOI: 10.1177/0022343316687017
|View full text |Cite
|
Sign up to set email alerts
|

The effects of military and non-military government expenditures on private consumption

Abstract: In this article, we provide evidence that civilian and military government spending have specific characteristics that can affect private consumption differently. Our vector autoregressive (VAR) estimates for the US economy for the period 1960-2013 show that civilian expenditure induces a positive and significant response on private consumption, whereas military spending has a negative impact. We also analyze the effects of these public spending components for the subsamples 1960-79 and 1983-2013, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Our DSGE model tries to explain the possible sources of crowding in/out effects in consumption observed in the data. To do so, we take into consideration heterogeneous households as in Galí et al (2007) and Lorusso and Pieroni (2017). A share of households does not have access to the bond market and consumes their current disposable income at each date.…”
Section: Introductionmentioning
confidence: 99%
“…Our DSGE model tries to explain the possible sources of crowding in/out effects in consumption observed in the data. To do so, we take into consideration heterogeneous households as in Galí et al (2007) and Lorusso and Pieroni (2017). A share of households does not have access to the bond market and consumes their current disposable income at each date.…”
Section: Introductionmentioning
confidence: 99%
“…32 As a robustness exercise, we have also estimated an SVAR model in the spirit of Lorusso and Pieroni (2017). Qualitatively, the results of the SVAR confirm the main transmission mechanisms predicted by our DSGE model.…”
Section: Productive Government Expenditurementioning
confidence: 53%
“…In this regard,Lorusso and Pieroni (2017) andBarro (1979) andBarro (1981) have stressed the importance of the economic effects of government spending and its alternative financing methods. In particular,Lorusso and Pieroni (2017) have focused on different public spending components, namely civilian and military expenditures.…”
mentioning
confidence: 99%
“…From the table, three empirical findings could be deduced irrespective of different estimation techniques deployed, country or countries studied as well as periods considered. The crowding-out effect of private investment by military spending, however, dominates the literature (Smith, 1980;Dreger, 1986;Knight, et al, 1996;Scott, 2001;Pieroni 2009;Hou and Chen, 2014;Malizard, 2015;Lorusso and Pieroni, 2017;Kennedy, 2021). This notwithstanding, a handful of studies concluded that military spending crowded-in investment (Üçler, 2016;Kollias and Paleologou, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%